Eyewitness to the Civil War : the complete history from secession to Reconstruction - Kagan, Neil.; Hyslop, Stephen G. (Stephen Garrison), 1950- (Washington, D.C. : National Geographic, 2006)
Records the military, political, social, and cultural history of the Civil War through photographs, artifacts, period illustrations, maps, essays by historians, and firsthand accounts.
Prologue : A nation divided -- 1861 : First blood -- 1862 : Total war -- 1863 : Victory or death -- 1864 : Rebels under siege -- 1865 : The final act -- Epilogue : The nation reunited.
Includes bibliographical references and index.
Keywords: United States -- History -- Civil War, 1861-1865 -- Personal narratives; United States -- History -- Civil War, 1861-1865 -- Pictorial works; United States; 1861 - 1865; History; Personal narratives; Pictorial works